Changing Trends of Marriage: Emerging Complication, Paradoxical Thinking and Social Transformation - Uprety, Mina Devi (Tri-Chandra Journal of Anthropology, 2024)
Marriage is one of the most ancient, indispensable, significant and universal social institution in all societies and cultures which has constructed since the beginning of human civilization. Marriage is a universal social phenomenon and it is a permanent bond between husband and wife which is intended to fulfill the economic, social, cultural, biological and emotional goals. Similarly, marriage establishes a new family which supports in giving facilities for the reproduction and upbringing of children. In changing context, individual freedom is greater matter rather than marital burden and partner’s ambiguity. In this modern era, there are various marriage allied complications, contradictions and changing trends. Sociological observations of marriage have brought out multifaceted marriage systems and its challenging transformations. Similarly, the change in gender relationship and independence between men and women has resulted in a considerable rise in the instability of marriage and its implication in the society. In this circumstance, this paper tries to analyze the conceptual and rational debates of orthodox and customary established marriage, marriage practice and its social, cultural, biological and emotional implications. Likewise, this study provides an analysis of contradictory thinking and declining trends of marriage in this contemporary society.